Studi Kasus: Program Fisioterapi pada Kondisi Carpal Tunnel Syndrome di RS Cakra Husada Klaten - Kevin Faizal Adhatama; Arif Pristianto; Sumarsono Sumarsono (Jurnal Kesehatan dan Fisioterapi, 2022)
Introduction: Carpal Tunnel Syndrome is a disorder of the limbs of the hand that causes pain and numbness, especially around the thumb, index finger, middle finger, and the radial side of the ring finger. In Indonesia, the incidence of Carpal Tunnel Syndrome is about 90% of various other neuropathy. Every year the incidence of Carpal Tunnel Syndrome reaches 267 out of 100,000 population with a prevalence of 9.2% in women and 6% in men.Objective: to determine the effect of giving interventions in the form of infrared, ultrasound, and exercise therapy in reducing pain, increasing muscle strength and increasing joint range of motion in Carpal Tunnel Syndrome conditions. Methods: conducted directly on 1 patient with Carpal Tunnel Syndrome condition with therapy given 3 times. The results were obtained after 3 sessions of therapy that there was a decrease in pain, an increase in muscle strength, and an increase in the range of motion of the joints. Conclusion: it can be said that a comprehensive physiotherapy program in the case of Carpal Tunnel Syndrome is proven to be able to reduce pain, increase muscle strength, and increase joint range of motion.Keywords: Carpal Tunnel Syndrome, Infra Red, Ultra Sound, Neural Mobilization, Exercise.